2023
DOI: 10.3389/fendo.2023.985858
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between metabolic dysfunction-associated fatty liver disease and the incidence rate of extrahepatic cancer

Abstract: BackgroundThe associations between metabolic dysfunction-associated fatty liver disease (MAFLD) and cancer development, especially extrahepatic cancers, are unknown. The aims of the current study were to investigate the cancer incidence rates of MAFLD and analyze the associations between MAFLD and the development of cancers.MethodsThis historical cohort study included participants who underwent ultrasonographic detection of hepatic steatosis at a tertiary hospital in China from January 2013 to October 2021. MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Other reports also demonstrated an increased cardiovascular mortality of patients with MAFLD as compared to NAFLD [ 9 ]. Similar results were also found in the risk of all types of cancers [ 10 ]. That means the transition from NAFLD to MAFLD helps identify more subjects who are at risk of extrahepatic events, and further promotes the surveillance of extrahepatic diseases in clinical practice.…”
supporting
confidence: 85%
“…Other reports also demonstrated an increased cardiovascular mortality of patients with MAFLD as compared to NAFLD [ 9 ]. Similar results were also found in the risk of all types of cancers [ 10 ]. That means the transition from NAFLD to MAFLD helps identify more subjects who are at risk of extrahepatic events, and further promotes the surveillance of extrahepatic diseases in clinical practice.…”
supporting
confidence: 85%
“…The number of people in the studies varied from 10,545 to 9,718,182. For the diagnosis of fatty liver, two studies ( 26 , 28 ) used ICD codes, two studies ( 31 , 32 ) utilized FLI, four studies ( 27 , 30 , 33 , 34 ) employed USG, and only one study ( 29 ) relied on liver biopsy. Most studies for confirming pancreatic cancer utilize ICD codes.…”
Section: Resultsmentioning
confidence: 99%
“…All studies revealed that confounders were taken into account ( Supplementary Table S2 ). Four studies ( 29 , 31 , 32 , 34 ) with a NOS score of 9 stars were considered to be of high quality, while five studies ( 26 28 , 30 , 33 ) with a NOS score of 7 or 8 stars were judged to be of medium quality in terms of methodological quality assessment (see Supplementary Table S3 for further details).…”
Section: Resultsmentioning
confidence: 99%
“…Family and community care of DFUs associated with MAFLD are essential links for rehabilitating diabetes foot ulcers. In addition, a previous study has demonstrated an independent relationship between MAFLD and an increased risk of cardiovascular disease (CVD), chronic kidney disease (CKD), cardiac remodelling, and cancer 19–21 . It follows that MAFLD must also be related to long‐term outcomes of T2DM, such as DFUs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a previous study has demonstrated an independent relationship between MAFLD and an increased risk of cardiovascular disease (CVD), chronic kidney disease (CKD), cardiac remodelling, and cancer. 19 , 20 , 21 It follows that MAFLD must also be related to long‐term outcomes of T2DM, such as DFUs. Therefore, exploring the association between MAFLD and DFUs is essential.…”
Section: Introductionmentioning
confidence: 99%